The Impact of COVID-19 on Commodity and S&P 500 Sector Return Volatility - Felton, James; McLaughlin, Dan; Yoo, Woongsun (Journal of Applied Business and Economics, 2024)
We investigate the impact of COVID-19 on commodity return volatility. We find that the impact of COVID-19 on return volatility is different across different markets. Unlike S&P 500 sector indices, commodity return volatility is less sensitive to the impact of COVID-19. The impact of vaccination programs on return volatility is weak for both commodity and financial markets. We employ Fama-French 3 Factor Model and APARCH (1,1) for return volatility estimation. The variation in COVID-19’s impact across different markets has an important implication for return volatility hedging.